An urgent need for building technical capacity for rapid diagnosis of multidrug-resistant tuberculosis (MDR-TB) among new cases: A case report from Maharashtra, India. Issue 5 (September 2015) - Atre, Sachin
Summary Multidrug-resistant tuberculosis (MDR-TB), the prevalence of which has increased across the globe in recent years, is a serious threat to public health. Timely diagnosis of MDR-TB, especially among new TB cases, is essential to facilitate appropriate treatment, which can prevent further emergence of drug resistance and its spread in the population. The present case report from India aims to address some operational challenges in diagnosing MDR-TB among new cases and potential measures to overcome them. It argues that even after seven years of implementing the DOTS-Plus program for controlling MDR-TB, India still lacks the technical capacity for rapid MDR-TB diagnosis. The case report underscores an urgent need to explore the use of WHO-endorsed techniques such as Xpert MTB/Rif and commercial assays such as Genotype MTBDR for rapid diagnosis of MDR-TB among new cases. Suitable applications may be found for other TB high-burden countries where MDR-TB is a major concern.